Synthesis and Photoactivity of Fe3O4/TiO2-Co as a Magnetically Separable Visible Light Responsive Photocatalyst - Eko Sri Kunarti; Indriana Kartini; Akhmad Syoufian; Karolina Martha Widyandari (Indonesian Journal of Chemistry, 2018)
Synthesis of magnetic photocatalyst, Fe3O4/TiO2-Co, with characterization and photoactivity examination have been conducted. The synthesis was initiated by preparation of Fe3O4 particles using coprecipitation method. The Fe3O4 particles were then coated with TiO2-Co at a various ratio of Fe3O4:TiO2 and concentration of Co(II) dopant. The Fe3O4/TiO2-Co was characterized by FTIR, XRD, TEM, SEM-EDX, VSM, and SR UV-visible methods. Photoactivity of the Fe3O4/TiO2-Co was carried out using methylene blue as a target molecule in degradation reaction within a batch system. By using optimum conditions, the degradation of methylene blue solution was performed under exposure to UV, visible light and dark condition. Results showed that the Fe3O4/TiO2-Co formation was confirmed by the presence of Fe3O4 and anatase diffraction peaks in the X-ray diffractogram. SR UV-Vis spectra indicated that the Fe3O4/TiO2-Co was responsive to visible light. Band gap energy of the Fe3O4/TiO2-Co with dopant concentration of 1; 5; 10 and 15% were 3.22; 3.12; 3.09 and 2.81 eV, respectively. The methylene blue solution can be well photodegraded at a pH of 10 for 210 min. The Fe3O4/TiO2-Co has the highest ability to methylene blue photodegradation with dopant concentration of 10% gave degradation yield of 80.51 and 95.38% under UV and visible irradiation, respectively.